Triple S Storage in Sand and Sprouting – testing a scaling strategy in Western Kenya - International Potato Center (2017)
The validation of the Triple S is nearing completion in western Kenya. Trials show that medium–sized roots stored in coarse sand for seven months produce viable planting material. There is a higher establishment rate and vigor in plots planted with vines sourced from Triple S beds compared to farmer selected material. A scaling strategy is being tested with 400 households, to identify the drivers which contribute to the uptake of the technology.